A drug-loaded mesoporous silica sustained-release system and preparation method thereof
Mesoporous silica was prepared by soft template method, and combined with impregnation method and chitosan coating technology, a mesoporous silica sustained release system was formed with drug-loaded mesoporous silica sustained release system, which solved the stability and sustainability of the existing drug-loading system in the treatment of inflammation or infection, achieved long-term and targeted drug release, and improved the therapeutic effect.
Patent Information
- Application Number
- CN202310387895.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-12
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-04-12
AI Technical Summary
The existing drug-loading system has problems such as poor stability, difficult to guarantee the duration of drug release, poor targeting and low bioavailability when treating inflammation or infection, especially when local medication is used, it is difficult to achieve accurate and long-term drug release.
Mesoporous silica was prepared by soft template method, and the drug was loaded by impregnation method, and finally coated with chitosan with ionic cross-linking method to form a mesoporous silica sustained release system with drug loaded.
The stability and biocompatibility of mesoporous silica are achieved, the drug load and release efficiency are improved, and the pH responsiveness can be used to release drugs in different microenvironments, which improves the effectiveness of anti-infection treatment.
Smart Images

Figure CN116605884B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a drug-loaded mesoporous silica sustained-release system and a preparation method thereof. Background Art
[0002] Inflammation or infection may cause the patient's body functions to decrease or even completely lose. Currently, the most effective treatment for inflammation and infection is the use of antibiotics. However, if systemic antibiotics are used to treat bone inflammation and infection, many adverse reactions will occur. In addition, since it is difficult to use the medicine accurately, it is difficult to ensure the local antibiotic concentration in the inflamed or infected area, which will inevitably prolong the medication time.
[0003] In view of the above problems, the use of drug delivery systems for local medication will effectively improve this situation, but drug-carrying systems such as liposomes and polymer micelles have poor stability. In addition, after the material is loaded with antibiotics, it cannot guarantee the duration of local antibiotic release, and the targeting is poor and the bioavailability is low. Mesoporous silica has the advantages of good pore structure, stability, low cytotoxicity, biocompatibility, etc. It is an ideal drug carrier material that can effectively improve the loading rate of drugs. Coating mesoporous silica can achieve controlled release of drugs.
[0004] The soft template method is a common method for preparing mesoporous silica. The template agent and organic additive will affect the pore size and morphology during the synthesis process. The organic additive can expand the pore size of the mesopores and increase the pore volume, thereby increasing the drug loading. Patent CN115215348A discloses a method for preparing worm-like mesoporous silica. By synthesizing a soft template agent, adding a silicon source to synthesize silica nanoparticles, no toxic template reagents are introduced during the preparation process, and ethanol is used as an organic additive. The commonly used organic additives in the process of preparing mesoporous silica using the soft template method are mesitylene, ethanol or a mixture of ethanol / ether. Mesitylene, as a benzene ring derivative, has high toxicity and pollutes the environment, while ethanol and a mixture of ethanol / ether are volatile, resulting in a decrease in concentration, and it is impossible to stably and accurately increase the pore size and pore volume.
[0005] Therefore, in the process of silica preparation, it is necessary to find a non-toxic and stable organic auxiliary agent, so that the carrier loaded with drugs can be selectively optimized, and the best carrier can be selected for coating to realize the sustained release function of the drug delivery system. Even when bacterial infection occurs, due to the production of acidic substances by bacterial metabolism, when the pH value of the microenvironment is slightly low, the drug-loaded mesoporous silica sustained-release system can still ensure the sustained release characteristics of the drug, thereby achieving better anti-infection treatment effects and helping to effectively prevent and treat bone infections. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing mesoporous silica;
[0007] The present invention further provides a drug-loaded mesoporous silica sustained-release system and a preparation method thereof.
[0008] The technical solution adopted to achieve the purpose of the present invention is:
[0009] The method for preparing a drug-loaded mesoporous silica sustained-release system of the present invention comprises the following steps:
[0010] Step 1: Preparation of mesoporous silica using soft template method
[0011] Weigh 50-200 mg of hexadecyltrimethylammonium bromide and 5-20 mg of polyether, dissolve in 24-120 mL of deionized water, stir evenly, add 88-700 μL of 2M NaOH solution, heat to 60-90°C for reflux; after reacting for 15 minutes, add 250-1000 μL of tetraethyl orthosilicate dropwise, and stir vigorously for 2 hours; dry the precipitate obtained by centrifuging the sample in an oven, then place the dried sample in a crucible, put it in a muffle furnace and calcine at 550°C for 5 hours to obtain mesoporous silica powder.
[0012] Step 2: Preparation of drug-loaded mesoporous silica using the impregnation method
[0013] (a) When the loaded drug is a liquid:
[0014] Mesoporous silica loaded with linezolid: Weigh 10 mg of mesoporous silica, add it to 4 mL of 2 mg / mL linezolid solution, add 200 μL of (3-aminopropyl)triethoxysilane, stir magnetically for 24 hours, centrifuge twice, and dry the resulting precipitate, which is the mesoporous silica loaded with linezolid.
[0015] (b) When the loaded drug is solid,
[0016] Mesoporous silica loaded with vancomycin: Weigh 10 mg of mesoporous silica, disperse it in 10 mL of deionized water, add 200 μL of (3-aminopropyl)triethoxysilane, then add 10 mg of vancomycin, stir for 24 hours, centrifuge twice, and dry the resulting precipitate, which is mesoporous silica loaded with vancomycin.
[0017] Step 3: Preparation of drug-loaded mesoporous silica sustained-release system
[0018] First, weigh 80 mg of chitosan, add it to 10 mL of 2% acetic acid solution, and slowly stir for half an hour to dissolve. Then weigh 5 mg of drug-loaded mesoporous silica, add it to the above solution and slowly stir for half an hour; then measure 10 mL of 0.5% sodium tripolyphosphate, add it to the above solution, and stir for half an hour to complete the coating; finally, centrifuge the sample, dry the precipitate, and obtain the drug-loaded mesoporous silica coated with chitosan, that is, use chitosan to complete the preparation of the drug-loaded mesoporous silica sustained-release system by ion crosslinking method.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention utilizes a soft template method to prepare mesoporous silica. The synthetic raw materials are non-toxic and non-polluting, the synthetic operation process is simple, the prepared mesoporous silica has good stability, good pore size and pore volume, good biocompatibility, and can effectively increase the drug loading capacity.
[0021] 2. The drug-loaded mesoporous silica sustained-release system can effectively prevent the premature release of drugs in the pores after coating the drug-loaded mesoporous silica, thereby achieving long-term drug release. It can effectively solve the problem of excessive drug release in current drug-loading systems, and has pH responsiveness. It can maximize the therapeutic effect of drugs under different microenvironments and has broad application prospects in the biomedical field. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a transmission electron microscope image of the mesoporous silica prepared in Example 1;
[0023] Figure 2 is a transmission electron microscope image of the mesoporous silica prepared in Example 2;
[0024] Figure 3 is a transmission electron microscope image of the mesoporous silica prepared in Example 3;
[0025] Figure 4 is a transmission electron microscope image of the mesoporous silica prepared in Example 4;
[0026] Figure 5 is a transmission electron microscope image of the mesoporous silica prepared in Example 5;
[0027] Figure 6 is a transmission electron microscope image of the mesoporous silica prepared in Example 6;
[0028] Figure 7 is a transmission electron microscope image of the mesoporous silica prepared in Example 7;
[0029] Figure 8 is a transmission electron microscope image of the mesoporous silica prepared in Example 8;
[0030] Fig. 9 is a nitrogen adsorption and desorption diagram of the mesoporous silica prepared in Example 5;
[0031] Fig.10 is a pore size distribution diagram of the mesoporous silica prepared in Example 5;
[0032] Fig.11 is a transmission electron microscope image of the mesoporous silica prepared in Example 5 after coating;
[0033] Fig.12 It is the drug release UV-visible absorption spectrum of the linezolid / mesoporous silica drug sustained-release system under the condition of pH=3 in Example 9.
[0034] Fig.13 is a drug release UV-visible absorption spectrum of the linezolid / mesoporous silica drug sustained-release system under the condition of pH=5 in Example 9;
[0035] Fig.14 is a drug release UV-visible absorption spectrum of the linezolid / mesoporous silica drug sustained-release system under the condition of pH=7 in Example 9;
[0036] Fig.15 It is a drug release curve diagram of the linezolid / mesoporous silica drug sustained-release system of the present invention under different pH conditions;
[0037] Fig.16 is a drug release UV-visible absorption spectrum of the vancomycin / mesoporous silica drug sustained-release system under the condition of pH=3 in Example 10;
[0038] Fig.17 is a drug release UV-visible absorption spectrum of the vancomycin / mesoporous silica drug sustained-release system under the condition of pH=5 in Example 10;
[0039] Fig.18 is a drug release UV-visible absorption spectrum of the vancomycin / mesoporous silica drug sustained-release system under the condition of pH=7 in Example 10;
[0040] Fig.19 It is a drug release curve diagram of the vancomycin / mesoporous silica drug sustained-release system of the present invention under different pH conditions. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0043] Example 1 Preparation of mesoporous silica
[0044] Weigh 50 mg of hexadecyltrimethylammonium bromide and 5 mg of polyether, dissolve in 24 mL of water, stir evenly, add 175 μL of 2M NaOH solution, heat to 70°C for reflux, react for 15 minutes, add 250 μL of tetraethyl orthosilicate dropwise, stir vigorously for 2 hours, centrifuge the sample to obtain a precipitate and dry it in an oven, then place the dried sample in a crucible, put it in a muffle furnace and calcine it at 550°C for 5 hours to obtain mesoporous silica powder. Figure 1 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 1.
[0045] Example 2 Preparation of mesoporous silica
[0046] The preparation method is the same as that in Example 1. After adding NaOH solution, the heating temperature is changed from 70°C reflux to 80°C reflux. Other conditions remain unchanged to obtain mesoporous silica powder. Figure 2 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 2.
[0047] Example 3 Preparation of mesoporous silica
[0048] The preparation method is the same as that in Example 1. After adding the NaOH solution, the heating temperature is changed from 70°C reflux to 90°C reflux, and other conditions remain unchanged to obtain mesoporous silica powder. Figure 3 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 3.
[0049] Example 4 Preparation of mesoporous silica
[0050] The preparation method is the same as that in Example 2. Hexadecyltrimethylammonium bromide and polyether are weighed, dissolved in water, stirred evenly, and then 88 μL of 2M NaOH solution is added. The mixture is heated to 80° C. for reflux. Other conditions remain unchanged to obtain mesoporous silica powder. Figure 4 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 4.
[0051] Example 5 Preparation of mesoporous silica
[0052] The preparation method is the same as that of Example 4. Hexadecyltrimethylammonium bromide and polyether are weighed, dissolved in water, stirred evenly, and then 175 μL of 2M NaOH solution is added. Other conditions remain unchanged to obtain mesoporous silica powder. Figure 5 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 5.
[0053] Example 6 Preparation of mesoporous silica
[0054] The preparation method is the same as that of Example 4. Hexadecyltrimethylammonium bromide and polyether are weighed, dissolved in water, stirred evenly, and then 350 μL of 2M NaOH solution is added. Other conditions remain unchanged to obtain mesoporous silica powder. Figure 1 This is a transmission electron microscope image of the mesoporous silica prepared in Example 1. Figure 6 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 6.
[0055] Example 7 Preparation of mesoporous silica
[0056] The preparation method is the same as that in Example 5, and the amount of raw materials used is twice that of the raw materials used in Example 1, namely: weigh 100 mg of hexadecyltrimethylammonium bromide and 10 mg of polyether, dissolve in 48 mL of water, stir evenly, add 350 μL of 2M NaOH solution, heat to 80°C for reflux. After reacting for 15 minutes, add 500 μL of tetraethyl orthosilicate dropwise and stir vigorously for 2 hours. The precipitate obtained by centrifugation of the sample is dried in an oven, and then the dried sample is placed in a crucible, placed in a muffle furnace and calcined at 550°C for 5 hours to obtain mesoporous silica powder. Figure 7 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 7.
[0057] Example 8 Preparation of mesoporous silica
[0058] The preparation method is the same as that in Example 7, and the amount of raw materials used is twice that of the raw materials used in Example 7 to obtain mesoporous silica powder. Figure 8 This is a transmission electron microscopy image of the mesoporous silica prepared in Example 8.
[0059] Example 9 Characterization Data of Mesoporous Silica
[0060] like Figure 1-3 It is a transmission electron microscope image of mesoporous silica prepared by changing the reflux temperature. By comparing the mesoporous silica prepared in Examples 1, 2, and 3, the results show that the mesoporous silica has good dispersibility. As the temperature increases, the particle size of the mesoporous silica increases. Clear mesoporous channels can be seen at a temperature of 80°C, and the average particle size is about 50nm. When the temperature rises to 90°C, the mesoporous channels are no longer obvious.
[0061] like Figure 4-6 It is a transmission electron microscope image of mesoporous silica prepared by changing the amount of NaOH under the condition of a reflux temperature of 80°C. By comparing the mesoporous silica prepared in Examples 4, 5, and 6, it can be seen that with the increase in the amount of alkali, the particle size of the mesoporous silica increases, and it changes from a monodisperse state to an aggregated state. When the amount is 175 μL, that is, the mesoporous silica prepared in Example 5 has good monodispersity, the mesopore channels are the clearest, and the average particle size is about 60 nm.
[0062] Figure 7-8 The transmission electron microscope image of mesoporous silica prepared by changing the amount of raw materials under the conditions of Example 5. The results show that Figure 5 In comparison, the amount of raw materials used is twice and four times that of the raw materials used in Example 5, respectively. As the amount of raw materials increases, the particle size of mesoporous silica increases, and it changes from a monodisperse state to an aggregated state. The proportion of mesoporous silica generated in the system decreases, and the pore structure gradually becomes less obvious.
[0063] Fig. 9 This is a nitrogen absorption and desorption diagram of the mesoporous silica prepared in Example 5, which has a characteristic curve of the mesoporous material. Fig.10 This is the pore size distribution diagram of mesoporous silica. The pore size distribution is calculated using the BJH method and the pore size is about 5nm.
[0064] Example 10 Preparation of the mesoporous silica drug-loaded sustained-release system prepared in Example 5
[0065] 10 mg of the mesoporous silica prepared in Example 5 was weighed and added to 4 mL of a 2 mg / mL linezolid solution, 200 μL of (3-aminopropyl)triethoxysilane was added dropwise, magnetic stirring was performed for 24 h, centrifuged twice, and the resulting precipitate was dried to obtain the mesoporous silica loaded with linezolid.
[0066] 10 mg of the mesoporous silica prepared in Example 5 was weighed and dispersed in 10 mL of deionized water. 200 μL of (3-aminopropyl)triethoxysilane was added dropwise, and then 10 mg of vancomycin was added. The mixture was stirred for 24 h, centrifuged twice, and the resulting precipitate was dried to obtain mesoporous silica loaded with vancomycin.
[0067] First, chitosan was used to coat the unloaded mesoporous silica by ion crosslinking. Fig.11 The figure shows a transmission electron microscope image obtained after coating the mesoporous silica prepared in Example 5, which shows that the mesoporous silica can be coated by using chitosan by ion crosslinking method.
[0068] Weigh 80 mg of chitosan and add it to 10 mL of 2% acetic acid solution, slowly stir for half an hour to dissolve, then weigh 5 mg of mesoporous silica loaded with linezolid and vancomycin, respectively, add them to the above solution and slowly stir for half an hour. Next, measure 10 mL of 0.5% sodium tripolyphosphate, add it to the above solution, and coat it after stirring for half an hour. Finally, centrifuge the sample, dry the precipitate, and obtain the mesoporous silica coated with the loaded drug, thus completing the preparation of the drug mesoporous silica sustained-release system.
[0069] Example 11 Drug sustained release experiment of mesoporous silica loaded with linezolid
[0070] Prepare buffer solutions of pH 3, 5, and 7, respectively. Take 7 portions of each pH buffer, 5 mL each, and take 5 mg
[0071] The mesoporous silica coated with linezolid prepared in Example 11 was placed in a buffer solution and the drug was released in vitro at a constant temperature for a total of 168 h. Samples were taken at intervals of 3 h, 6 h, 12 h, 24 h, 72 h, 120 h, and 168 h, and the absorbance of the drug was measured. Figure 12-14 , Fig.15 This is the drug release curve of the linezolid / mesoporous silica drug sustained-release system under different pH conditions.
[0072] Example 12 Drug sustained release experiment of mesoporous silica loaded with vancomycin
[0073] The other experimental steps were the same as those in Example 10, except that the loaded drug was changed from linezolid to vancomycin for sustained release experiments. The experimental conditions remained unchanged, and the drug release was carried out for a total of 168 h. Samples were taken at intervals of 3 h, 6 h, 12 h, 24 h, 72 h, 120 h, and 168 h, and the absorbance of the drug was measured as shown in FIG. Figure 16-18 , Fig.19 This is the drug release curve of vancomycin / mesoporous silica drug sustained-release system under different pH conditions.
[0074] Example 13 Analysis of drug sustained release test results
[0075] When a bacterial infection occurs in the body, the pH value of the microenvironment is slightly lower due to the production of acidic substances by bacterial metabolism, and the pH value of the microenvironment will also change over time. Figure 12-14 , 16-18 are the UV-visible absorption spectra of the drug-loaded mesoporous silica sustained-release system for sustained-release of linezolid and vancomycin at different pH values. It can be seen that the drug release rate and amount are different under different pH conditions, indicating that the drug-loaded mesoporous silica sustained-release system is pH responsive; in acidic and neutral environments, the continuous drug release time can exceed 160 hours through the pH-responsive mesoporous silica drug-loaded sustained-release system.
[0076] like Fig.15 and 19 As shown in the figure, the mesoporous silica drug-loaded sustained-release system is monitored every 40 hours. The monitoring results show that the lower the pH, the less the amount of drug released. When the drug release time is the same, the drug release rate and amount are the highest under the condition of pH = 7, which means that the drug can be released for a longer time under high pH conditions, but in an environment with slightly lower pH values, the mesoporous silica drug-loaded sustained-release system can still release drugs for a long time, thereby achieving better anti-infection treatment effects.
[0077] Therefore, the mesoporous silica drug-loaded sustained-release system of the present invention is not only pH-responsive, but also can maintain a good sustained-release effect under different microenvironments, which is helpful for the effective prevention and treatment of bone infection.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A drug-loaded mesoporous silica sustained-release system, characterized in that: The drug-loaded mesoporous silica surface only needs to be coated with a chitosan shell; The drug-loaded mesoporous silica is obtained by loading antibiotic drugs on the mesoporous silica using an impregnation method and drying the mesoporous silica. The mesoporous silica is prepared by using a soft template method with polyether as an organic auxiliary agent. 50-100 mg of hexadecyltrimethylammonium bromide and 5-10 mg of polyether are dissolved in deionized water, 175 μL of a 2M NaOH solution is added, and the mixture is heated to 80° C. for reflux. After a period of reaction, 250-500 μL of tetraethyl orthosilicate is added. The obtained sample is centrifuged, dried, and then calcined at high temperature to obtain the mesoporous silica.
2. A drug-loaded mesoporous silica sustained-release system as claimed in claim 1, characterized in that: The antibiotic drugs are linezolid and vancomycin.
3. The method for preparing a drug-loaded mesoporous silica sustained-release system according to claim 1, characterized in that: Chitosan was added to a 2% acetic acid solution, stirred to dissolve, and then drug-loaded mesoporous silica was added, followed by sodium tripolyphosphate at a concentration of 0.5%. After stirring for 0.5 h, the coating was completed. The sample was centrifuged and dried to obtain a drug-loaded mesoporous silica sustained-release system coated with chitosan.
Citation Information
Patent Citations
Preparation method of wormlike mesoporous silica
CN115215348A
Chitosan-modified pH responsive medicine-loading controlled release material and preparation method thereof
CN103920153A
Synthesis method of monodispersed nano-mesopore silicon dioxide material
CN1618735A
Cited By
Water-based silicon-based nano sustained-release body and preparation method thereof
CN121465008A